2022
DOI: 10.1038/s41467-022-32086-6
|View full text |Cite
|
Sign up to set email alerts
|

A unique class of Zn2+-binding serine-based PBPs underlies cephalosporin resistance and sporogenesis in Clostridioides difficile

Abstract: Treatment with β-lactam antibiotics, particularly cephalosporins, is a major risk factor for Clostridioides difficile infection. These broad-spectrum antibiotics irreversibly inhibit penicillin-binding proteins (PBPs), which are serine-based enzymes that assemble the bacterial cell wall. However, C. difficile has four different PBPs (PBP1-3 and SpoVD) with various roles in growth and spore formation, and their specific links to β-lactam resistance in this pathogen are underexplored. Here, we show that PBP2 (kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 62 publications
4
10
0
1
Order By: Relevance
“…In vitro data indicate that the zinc ion is required for protein stability, whereas metal deprivation does not preclude β-lactam binding, suggesting the Zn-depleted TPase site retains structural integrity to a certain extent. Our findings are in line with recent structures of Clostridium difficile bPBPs operative in PG synthesis during vegetative growth (PBP2) and sporogenesis (PBP3 and SpoVD), showing an analogous TPase Zn site that is critical for protein stability and affects β-lactam binding ( 47 , 48 ). It is worth noting that the Zn site in A. baumannii PBP2 (D-x14-D-x5-H-x12-C) and C. difficile bPBPs (D-x12-D-x9-H-x12-C in PBP2, C-x14-C-x5-H-x12-C in PBP3, and C-x12-C-x6-H-x12-C in SpoVD) can tolerate some variation in the metal ligation residues and their relative position in the polypeptide sequence.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In vitro data indicate that the zinc ion is required for protein stability, whereas metal deprivation does not preclude β-lactam binding, suggesting the Zn-depleted TPase site retains structural integrity to a certain extent. Our findings are in line with recent structures of Clostridium difficile bPBPs operative in PG synthesis during vegetative growth (PBP2) and sporogenesis (PBP3 and SpoVD), showing an analogous TPase Zn site that is critical for protein stability and affects β-lactam binding ( 47 , 48 ). It is worth noting that the Zn site in A. baumannii PBP2 (D-x14-D-x5-H-x12-C) and C. difficile bPBPs (D-x12-D-x9-H-x12-C in PBP2, C-x14-C-x5-H-x12-C in PBP3, and C-x12-C-x6-H-x12-C in SpoVD) can tolerate some variation in the metal ligation residues and their relative position in the polypeptide sequence.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, our bioinformatic analysis suggests that Zn-binding PBPs are present in aerobic bacteria and widespread in β- and γ-Proteobacteria. These results expand on previous findings of Zn-binding PBPs largely in anaerobic bacteria and the phylum Firmicutes ( 47 ) and together provide a broad picture of the zinc PBP distribution across the bacterial kingdom. The physiological relevance of the conserved Zn site in the bPBPs of A. baumannii and other selected bacteria has yet to be fully elucidated.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The molecular mechanisms by which MreE mutations increase resistance to specific classes of beta-lactam antibiotics [7] [8,9] are as yet undefined and may include reduced binding affinity of affected antibiotic classes, in addition to interaction with other genomic loci that can produce higher levels of resistance, a finding suggested by the fact that transfer of the mreE alleles alone into susceptible strains did not elevate most cephalosporin MICs to the level of the original parent strain (Fig 2C). The gene-level variants also provide targets to aid in the detection of cephalosporin resistance, whether by strain genomic analyses or with targeted mreE probes to evaluate primary patient samples for resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…An intrinsic class D beta-lactamase providing degress of resistance across genomically diverse C. difficile has been identified [5,6]. Variants in the pathogen's penicillin-binding protein 2 (PBP2) have also been identified that have reduced binding-affinity to certain beta-lactam classes, including cephalosporins and carbapenems [7]. However, causative effects of these variants on phenotypic resistance in vitro and in vivo have not yet been defined, limiting our understanding of their role in patient disease [8][9][10].…”
Section: Introductionmentioning
confidence: 99%